PENDEKATAN EUROPEAN FOUNDATION FOR QUALITY MANAGEMENT (EFQM) UNTUK EVALUASI DALAM PENINGKATAN KINERJA ORGANISASI SECARA BERKELANJUTAN - Tamara Rahma Widowati; Aufa, Muhammad Izzul; Nurdiansyah, Rudi; Izzul, Muhammad (Teknik Industri Unikom, 2025)
Increasing competition drives companies to adopt performance measurement tools that ensure continuous improvement. This study assesses and improves the performance of PT. XYZ, a developing plywood manufacturer, using the European Foundation for Quality Management (EFQM) model. An explanatory quantitative approach was applied with data from 110 employees through validated and reliable questionnaires. The company scored 698 out of 1000, indicating high performance. Strengths were found in Purpose, Vision, and Strategy, while weaknesses appeared in Organizational Culture and Leadership, Driving Performance and Transformation, and Creating Sustainable Value. Significant correlations were identified between the Direction and Execution dimensions and Stakeholder Perception. Recommendations include strengthening organizational culture, enhancing human resource development, and regularly evaluating stakeholder perceptions. The EFQM model proves effective as a framework for guiding sustainable performance improvement.